Kinetika Reaksi Transesterifikasi CPO Ber-FFA Tinggi Dengan Menggunakan Katalis ZnO Sintesis - Irwanda, Juni; Helianty, Sri; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Synthesized catalyst ZnO precipitant zinc oxalate was used as the catalyst for converted Crude Palm Oil (CPO) which has a high Free Fatty Acid (FFA) into methyl ester. This research is aimed to determine the kinetics of transesterification reaction of high FFA CPO to methyl ester with that catalyst. The data of kinetics transesterification reaction is done by isolation technique that is by comparison of mole ratio of CPO : methanol 1: 18. Kinetic of transesterification was carried out at different temperatures (45 - 65°C) and different times of reaction (0 - 60 minutes). The effects of temperatures and time of the reaction rate constant were investigated. The result showed that content of methyl ester increased with the increasing of the reaction temperatures. The highest content of methil ester of 97,7% was obtained at 65°C and 60 minutes of reaction time. The rate constant of transesterification was determined by employing integral and differential method with the overall chemical reaction following the pseudo first order reaction. The activation energy was 36,55 kJ/mol.Keywords: kinetic, methyl ester, transesterification, ZnO catalyst